Life cycle assessment of intensive striped catfish farming in the Mekong Delta for screening hotspots as input to environmental policy and research agenda. - Bosma, Roel
Purpose Intensive striped catfish production in the Mekong Delta has, in recent years, raised environmental concerns. We conducted a stakeholder-based screening life cycle assessment (LCA) of the intensive farming system to determine the critical environmental impact and their causative processes in producing striped catfish. Additional to the LCA, we assessed water use and flooding hazards in the Mekong Delta. Materials and methods The goal and scope of the LCA were defined in a stakeholder workshop. It was decided there to include all processes up to the exit gate of the fish farm in the inventory and to focus life cycle impact assessment on global warming, acidification, eutrophication, human toxicity and marine (MAET) and freshwater aquatic ecotoxicity (FWET). A survey was used to collect primary inventory data from 28 farms on fish grow out and from seven feed mills. Hatching and nursing of striped catfish fingerlings were not included in the assessment due to limited data availability and low estimated impact. Average feed composition for all farms had to be applied due to limitation of budget and data availability. Results and discussion. Feed ingredient production, transport and milling dominated most of the impact categories in the LCA except for eutrophication and FWET. Most feed ingredients were produced outside Vietnam, and the impact of transport was important. Because of the screening character of this LCA, generic instead of specific inventory data were used for modelling feed ingredient production. However, the use of generic data is unlikely to have affected the main findings, given the dominance of feed production in all impact categories. Of the feed ingredients, rice bran contributed the most to global warming and acidification, while wheat bran contributed the most to eutrophication. The dominance of both was mainly due to the amounts used. Fishmeal production, transport and energy contributed the most to MAET. The biggest impacts of grow out farming in Vietnam are on eutrophication and FWET. Water nutrient discharge from grow out farming was high but negligible compared with the natural nutrient content of the Mekong River. The discharge from all growout farms together hardly modified river water quality compared with that before sector expansion. Conclusions Feed production, i.e. ingredient production and transport and milling, remains the main contributor to most impact categories. It contributes indirectly to eutrophication and FWET through the pond effluents. The environmental impact of Pangasius grow out farming can be reduced by effectively managing sludge and by using feeds with lower feed conversion ratio and lower content of fishery products in the feed. To consider farm variability, a next LCA of aquaculture should enlist closer collaboration from several feed milling companies and sample farms using their feeds. Future LCAs should also preferably collect specific instead of generic inventory data for feed ingredient production, and include biodiversity and primary production as impact categories.
Keywords: Aquaculture; Environmental impact; LCA; Pangasius; Striped catfish; Vietnam